THE EFFECTIVENESS OF PROJECT-BASED LEARNING MODELS IN IMPROVING UNDERSTANDING OF STATISTICAL CONCEPTS - Nurul Astuty Yensy; Rambat Nur Sasongko; Muhammad Kristiawan; Dina Apryani; Hidayatulloh Hidayatulloh (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Every student in higher education will learn about statistics. Statistics is knowledge about data collection, data classification, presentation, processing, drawing conclusions, and making decisions based on certain problems. Because statistics are related to sample data, it is necessary the ability to interpret, understand, and make good decisions on the data. Project-Based Learning is very suitable to be applied to solve complex problems in a creative, collaborative, and independent way like in this course. This research is to analyze the effectiveness of PjBL learning in improving the understanding of statistical concepts. The research subjects were seventy students who took statistics courses at the Mathematics Education Study Program, Bengkulu University in 2021. This type of research is a quasi-experimental design using a one-group pretest-posttest design. The research instrument was a test sheet for understanding the concept of statistics, including the ability to choose statistical analysis, the ability to process data, and the ability to interpret the results. The data were analyzed using the t-paired sample test and the N-Gain score. Based on the results of the study, it can be concluded that the application of Project-Based Learning is quite effective in increasing students' understanding of concepts in statistics courses at Bengkulu University, especially in the mathematics education study program. Students' understanding of concepts after the PjBL model is applied is higher than before PjBL is applied.Setiap mahasiswa di perguruan tinggi pasti akan mempelajari tentang statistika. Statistika merupakan pengetahuan mengenai pengumpulan data, klasifikasi data, penyajian, pengolahan, penarikan kesimpulan, dan pengambilan keputusan berdasarkan masalah tertentu. Dikarenakan statistik berkaitan dengan data sampel maka diperlukan kemampuan pemahaman dalam menafsirkan, memahami serta membuat keputusan yang baik terhadap data tersebut. Model Project Based Learning sangat cocok diterapkan untuk memecahkan masalah kompleks dengan cara yang kreatif, kolaboratif, dan mandiri seperti pada mata kuliah ini. Penelitian ini dilakukan untuk menganalisis efektifitas model pembelajaran PjBL dalam meningkatkan pemahaman konsep statistika. Subjek penelitian yaitu tujuh puluh mahasiswa yang mengambil mata kuliah statistika di Program Studi Pendidikan Matematika Universitas Bengkulu tahun 2021. Jenis penelitian adalah quasi eksperiment dengan menggunakan rancangan one group pretest-postest design. Instrumen penelitian berupa lembar tes pemahaman konsep tentang statistika, meliputi kemampuan memilih analisis statistika, kemampuan pengolahan data dan kemampuan menginterpretasikan hasilnya. Data dianalisis dengan menggunakan uji t-paired sample dan skor N-Gain. Berdasarkan hasil penelitian dapat disimpulkan bahwa penerapan model pembelajaran Project Based Learning cukup efektif untuk meningkatkan pemahaman konsep mahasiswa pada mata kuliah statistika di Universitas Bengkulu khususnya di program studi pendidikan matematika. Pemahaman konsep mahasiswa setelah diterapkan model PjBL lebih tinggi dibandingkan sebelum diterapkan PjBL.